Banker directors and firm performance: Are family firms different? - Saibal Ghosh (Future Business Journal, 2018)
Employing data on publicly listed Indian manufacturing firms covering the period 1996-2012, we investigate the impact of the presence of banker-director on the board of family firms. We posit several hypotheses that highlight the pros and cons of the presence of banker-directors. The findings provide support to the industry expertise hypothesis which suggests that bankers are less likely on boards on family firms that operate in industries where the possibilities of knowledge spillovers can significantly influence profits. A disaggregated analysis suggests that the performance of these firms varies depending on the nature of equity and ownership interlocking.
Keywords: G34; L26; P52; 650; Banker-director; Corporate governance; Family firms